Evaluation of depressive symptoms of family caregivers of the Family Health Strategy (ESF) Adamantina Garden; Adamantina-SP (Research, Society and Development, 2022)
Depression is a serious and highly prevalent problem in the general population. Some sociocultural factors and individual life situations can trigger such a situation or have an effect on its prevalence, and one of these is the situation of the family caregiver that is addressed in this study. The emergence of family caregivers, together with their impacts and problematizations, emerged and increased mainly for two reasons: the psychiatric deinstitutionalization process and the demographic transition. The objective of this study was to analyze the presence of depressive symptoms in family caregivers in the ESF of Jardim Adamantina. Field research was carried out in the homes of caregivers of patients registered at UBS Jardim Adamantina, who need daily care, and subsequent delivery of identification sheets and questionnaire from the Beck Depression Inventory (BDI-II) for tracking and evaluation. After delivery of the forms, a quantitative-qualitative analysis of the results obtained was carried out and the consequent interpretation of the problems obtained. The results showed the prevalence of women in the occupation of parental care activities (79%), with a higher rate of depressive symptoms compared to the men interviewed (46% of women, against 14% of men). The overall mean age of the group was 55 years, with 52 years being the mean age of symptomatic caregivers. Patients were requested to be referred to a psychiatrist for a consultation with a specialist doctor, if they agreed, and, if possible, to sensitize other family members to assist in tutoring. Therefore, analyzed later to find out whether or not there was an improvement in the lives of these caregivers.